The income-labour nexus as the dominant institutional form in rural sub-Saharan Africa. How youth transition helps to understand structural change - (:unkn) unknown (My University, 2022)
The unprecedented population growth and low economic diversification in sub-Saharan Africa (SSA) raise questions about possible paths for demo-economic transitions. Given the limitations of the dominant macroeconomic conception of structural change for analysing economic transformations in SSA, and acknowledging the importance of rural economies in SSA, this paper argues for an alternative approach to structural change that uses the rural household as the key unit of analysis of change. Structural change is therefore impacted by the evolution of the socioeconomic reproduction patterns of rural households. To understand these households' reproduction patterns, the paper formulates an analytical framework centred on structures, institutions and their evolution. Drawing on Régulation theory, we first adjust institutional forms to rural African contexts. We then demonstrate how the income-labour nexus, integrating the social relations linked to the organisation of the production process and the modes of reproduction, is the dominant institutional form in capturing the socioeconomic reproduction of rural households. Last, to detect these emerging institutional configurations, we analyse youth transition as the critical period of households' socioeconomic reproduction that can reveal structural change.
Keywords: African Research